Acting & theatre - Evans, Cheryl; Smith, Lucie (Tulsa, Okla. : EDC Pub., 1992)
Presents an introduction to acting and theatre, gives a brief history of drama, and a brief survey of some of the world's better-known playwrights.
Includes index.
Book Links (A.L.A.).
Young Adult
Keywords: Acting -- Technique; Drama -- History; Acting -- Technique; Drama -- History